Islam in the eyes of Girolamo Savonarola (1452-1498) - Garczyński, Dawid (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The aim of the article is to show islam in the eyes of Girolamo Savonarola and show its confrontation with what religion should be according to the dominican. The first part will describe the figure of Muhammad, the founder of islam. The second part will be devoted to the followers of mohammedanism and their holy book, the Quran. The third part will present an assessment of islam in terms of its usefulness for spiritual development. The analyses carried out allow the following conclusions to be drawn. First, Muhammad was not a true spiritual leader, but contrary to the example of Jesus Christ, instead of prevailing with truth, he resorted to force. Secondly, the good teachings of the Quran did not reach the muslims because it is full of contradictions. They were guided by the sinful human nature that islam fueled. Third, islam is not useful for spiritual development, but was used as a tool to achieve the desires and ambitions of its founder, Muhammad, and as such can still serve. These conclusions show the overall view of Girolamo Savonarola on islam and his subjective and emotional assessment. For a dominican, it is a competution, one of the dangers announced by Jesus Christ, which the Church must suffer, but will undoubtedly survive.